Glutathione System and Oxidative Stress in Health and Disease - Dulce Bagatini, Margarete (Biochemistry, 2020)
The imbalance between the production of reactive oxygen species (ROS) and antioxidant defenses determines a state known as oxidative stress. Higher levels of pro-oxidants compared to antioxidant defenses may generate oxidative damage, which, in turn, may lead to modifications in cellular proteins, lipids, and DNA, reducing functional capacity and increasing the risk of diseases. Nevertheless, the clearance of harmful reactive chemical species is achieved by the antioxidant defense systems. These protection systems are referred to as the first and second lines of defense and comprise the classic antioxidants, enzymatic and nonenzymatic defenses, including glutathione. This book presents and discusses the advancement of research on health and diseases and their underlying mechanisms, exploring mainly aspects related to the glutathione antioxidant system.